HEMATOPHAGOUS INSECTS IN THE FOSSIL RECORD - Lukashevich E.D.; Mostovski M.B. (My University, 2003)
Hematophagous insect fossils are reviewed. The origin of hematophagy in various dipteran groups is discussed.